Pemberdayaan guru IPA: Integrasi strategi understanding by design untuk meningkatkan kompetensi profesional dalam mendesain rencana pembelajaran - Mahdiannur, Muhamad Arif; Martini, Martini; Astriani, Dyah; Setiawan, Beni; Qosyim, Ahmad (STAI Auliaurrasyidin Tembilahan, 2024)
Improving teachers' competence in designing learning is essential for the quality of education. Many teachers struggle to develop effective lesson plans. This program aims to enhance the competence of science teachers in junior high schools in East Java through a hybrid workshop (offline and online) using the Understanding by Design (UbD) approach. The target participants were members of the Science Teachers' Association (MGMP). The program's effectiveness was assessed using a one group pre-posttest design, analyzed with raincloud plots, and the shift in pretest-posttest scores was evaluated using histograms and contingency tables. The results showed that the majority of participants experienced improvement, with 80% shifting to higher performance categories. The workshop successfully assisted teachers in developing lesson plans that align with student characteristics and curriculum goals. The long-term impact of the program is the enhancement of science teachers' pedagogical and pedagogical content knowledge.